Analysis of The Impact of Talent Management Practices on Organizations and Human Resources in Batam City - Sentoso, Antony; Mon, Muhammad Donal; Annisah, Tiara (Universitas Pamulang, 2024)
The research aims to analyze the impact of talent management practices on organizational performance as well as human resources in the four-star hospitality industry sector in Batam City. The research uses quantitative methods as well as the application of SPSS as an analysis tool. Has respondent results with data from 251 hospitality employees using Google forms as a medium for the dissemination of questionnaires. The results of the research show that talent attraction and talent development have a significant positive impact on organizational performance as well as human resources. However, talent retention has no significant impact on the performance of the organization and the human resource. Thus, talent management practices such as talent attraction and talent development can be important factors in improving corporate performance and human resources in the four-star hospitality industry in Batam City. This research contributes to understanding how talent management practices can have an impact on organizational performance as well as human resources in the hospitality sector. These results can provide guidance for companies in developing more effective human resource management strategies for organizational goals and sustainable growth.